Creativity and Academic Achievement: A Meta-Analysis Study Article - Akpur, Ugur (European Scientific Journal, ESJ, 2023)
The ability to think and act creatively is significant for individuals as well as societies. Within the context of education, creativity is considered as one of most the fundamental aspects of cognitive development. In this respect, the purpose of the current study was formed to investigate the impact of creativity on academic achievement. To that goal, a meta-analytic approach was applied in this study with the aim of synthesizing the findings from different research, and studies published in Academic Search Ultimate Database, ERIC and SCOPUS between 2005 and 2022 were included in the analysis. The meta-analysis was confined solely to studies that investigated the relationship between the variables, therefore the correlation coefficient was specified as an indicator to determine the effect size. After reviewing in accordance with the inclusion criteria, 18 relevant papers with a total sample size of 6846 were included in the study. The results revealed that the overall effect size of creativity on academic achievement was .619, which points out the medium effect size. The findings of study and their implications were discussed.